Clove oil as a neuromodulator in environmental cadmium cognitive impairment on the prefrontal cortex of Wistar rats - Obinna O. Uchewa; Chinedu B. Egwuagu; Ogugua A. EGWU; Augustine O. Ibegbu (Journal of Trace Elements and Minerals)
Background: Trace elements in the environment are neurotoxins and severely affect the nervous system, which can impair cognitive ability. Objective: To investigate the neuromodulatory role of clove oil (CLO) in Cd-induced cognitive impairment. Methods: Thirty-five Wistar rats randomly assigned into five groups of seven were used. Group A received water, group B received 20 mg/kg of Cd, C received 10 mg/kg of CLO, D received 20 mg/kg of CLO, and E received 20 mg/kg of DMSO. All groups except A received 20 mg/kg of Cd before treatment. Sociability Chamber Tests (SCT) and Novel Object Recognition Tests (NORT) were used to test recognition memory as social behavior in rodents. The estimated GST, GPx, GSH, and GOT enzymes were by blood sample. Results: GSH and GST levels significantly decreased in the untreated but increased in the treated groups at P < 0.05. The discrimination index reduced in the untreated group (p < 0.05) while the reduction continued in groups C and E (0.14±0.09 and 0.27±0.02), and group D increased (0.81±0.02). In the SCT, group B spent significant time in the common chamber, which increased significantly in groups C and D but decreased in E. Microscopically, group A showed normal histoarchitecture and several alterations in group B. In contrast, treated groups showed improvement in cell regeneration. Conclusion: Clove oil alleviates cadmium toxicity by increasing antioxidant activity and improving cognition in rats.